Cerebral metastases of endometrial carcinoma. Diagnostic and neurosurgical aspects - N. V. Sevyan; V. B. Karakhan; Yu. A. Tsybulskaya; Yu. V. Bondarenko (ABV-press, 2014)
Central nervous system (CNS) involvement by endometrial carcinoma is uncommon. Among 1710 patients registered for brain metastases at our institution between 1990 and 2012, 3 (0.18 %) developed brain metastases. All lesions (1 multiple, 2 single) were contrast enhancing on com- puted tomography scans, and were located in the cerebrum (lobus occipitalis) in 2 cases. The CNS was the only site of detectable disease in 1 patient with recurrent disease. One patient received radiotherapy (survival, 3 months) and two underwent surgical resection of solitary metas- tasis followed by radiotherapy (survival = 3 and 5 months and alive to the present). Prognosis of patients with CNS metastases from endometrial carcinoma appears poor; however, in a selected group of patients early diagnosis followed by multimodal treatment may result in a palliation of the disease.